Expanding the clinical spectrum of Fowler syndrome: Three siblings with survival into adulthood and systematic review of the literature. Issue 5 (11th May 2020) - De Luca, Chiara; Crow, Yanick J.; Rodero, Mathieu; Rice, Gillian I.; Ahmed, Melek; Lammens, Martin; De Cock, Paul; Van Esch, Hilde; Lagae, Lieven; Rochtus, Anne
Abstract: Proliferative vasculopathy and hydranencephaly‐hydrocephaly syndrome (PVHH, OMIM 225790), also known as Fowler syndrome, is a rare autosomal recessive disorder of brain angiogenesis. PVHH has long been considered to be prenatally lethal. We evaluated the phenotypes of the first three siblings with survival into adulthood, performed a systematic review of the Fowler syndrome literature and delineated genotype‐phenotype correlations using a scoring system to rate the severity of the disease. Thirty articles were included, describing 69 individual patients. To date, including our clinical reports, 72 patients have been described with Fowler syndrome. Only 6/72 (8%) survived beyond birth. Although our three patients carry the same mutations (c.327T>A‐p.Asn109Lys and c.887C>T‐p.Ser296Leu) in FLVCR2, only two of them presented with the same cerebral features, ventriculomegaly and cerebral calcifications, as affected fetuses. The third sibling has a surprisingly milder clinical and radiological phenotype, suggesting intrafamilial variability. Although no clear phenotype‐genotype correlation exists, some variants appear to be associated with a less severe phenotype compatible with life. As such, it is important to consider Fowler syndrome in patients with gross ventriculomegaly, cortical malformations and/or cerebral calcifications on brain imaging. Abstract :